Gamma-ray shielding nanofiber membrane with core-shell structure and preparation method of gamma-ray shielding nanofiber membrane
By using the nuclear shell structure to shield the nano -fiber membrane, using the surface modified heavy metal micro -nano particles and polymer polymers to prepare through electrostatic spinning technology to solve the problem of large weight and poor breathability of traditional γ -ray shielding materials. A light and efficient γ -ray shielding effect is achieved.
Patent Information
- Application Number
- CN202411538703.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional gamma-ray shielding materials have problems such as large weight, poor breathability, difficulty in processing, and poor flexibility, which are difficult to meet the lightweight, flexible and efficient gamma-ray shielding needs.
The γ -ray shielding nanofiber film with a nuclear shell structure is composed of surface modified heavy metal micro -nano particles and polymer polymers. It is prepared by electrostatic spinning technology to form a multi -layer structure of the shell layer and nuclear layer to improve the shielding shielding performance.
The lightweight and efficient γ -ray shielding performance is realized, and it has good mechanical performance and processing performance. It is suitable for the application of nuclear radiation scenarios under permeability and humidity conditions.
Smart Images

Figure CN119372837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of synthesis and preparation of organic-inorganic hybrid materials, and in particular relates to a gamma-ray shielding nanofiber membrane with a core-shell structure and a preparation method thereof. Background Art
[0002] With the continuous development of nuclear technology and radioactive applications, the demand for high-performance gamma-ray shielding materials is growing. Traditional gamma-ray shielding materials, such as heavy metal plates or concrete, often have problems such as heavy weight, difficult processing, and poor flexibility, which limit their application in some special fields. Therefore, the development of lightweight, flexible and efficient gamma-ray shielding materials has important scientific and practical value.
[0003] As a simple and effective method for preparing nanofibers, electrospinning technology has shown great potential in the preparation of high-performance X-ray / γ-ray shielding materials. Studies have shown that nanofiber membranes prepared by electrospinning have good X-ray shielding properties. These nanofiber membranes are mainly composed of polymers and inorganic nanofillers. As a matrix, polymers provide good mechanical properties and processing properties; while inorganic nanofillers play a role in enhancing shielding performance. At present, commonly used inorganic nanofillers include metal oxides (such as iron oxide, tungsten oxide, etc.), metal powders (such as iron, tungsten, etc.) and rare earth element compounds.
[0004] In the process of preparing X-ray shielding nanofiber membranes, factors such as the diameter, morphology, orientation of nanofibers and the dispersion state of fillers have an important influence on the shielding performance. By optimizing these parameters, the shielding performance of nanofiber membranes can be further improved. In addition, some researchers have also tried to use multi-nozzle electrospinning technology to prepare composite nanofibers with different compositions and structures to achieve better shielding effects. For example, the relevant literature (DOI: 10.1002 / admt.202300760) reported the use of electrospinning technology to prepare green, efficient and radiation-resistant nanofiber membranes composed of cellulose fluorescent particles (CFP), ZnO-Bi2O3 nanoparticles and polyacrylonitrile (PAN) solution. This nanofiber membrane not only has excellent ultraviolet interception performance, but also has a strong shielding effect on low-energy X-rays, and is suitable for daily life products, such as ultraviolet and X-ray radiation protective clothing. Although relevant research has been conducted on the preparation of X / γ-ray shielding nanofiber membranes by electrospinning, there are still some challenges, such as how to further improve the shielding performance of nanofiber membranes and achieve lightweight, breathable and moisture-permeable and efficient γ-radiation protection.
[0005] Therefore, in order to overcome the above technical problems, it is necessary to provide a core-shell structured γ-ray shielding nanofiber membrane and a preparation method thereof. Summary of the invention
[0006] The present invention relates to a core-shell structured gamma-ray shielding nanofiber membrane and a preparation method thereof, aiming to provide a lightweight, breathable and moisture-permeable, flexible and efficient gamma-ray shielding material to solve the problems of traditional gamma-ray shielding materials such as heavy weight, poor air permeability, difficult processing and poor flexibility.
[0007] The technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a core-shell structured γ-ray shielding nanofiber membrane, comprising the following steps:
[0009] S1 Surface modification of heavy metal micro-nano particles: Use a surface modifier to modify the surface of heavy metal micro-nano particles so that the surface of the heavy metal micro-nano particles has functional groups;
[0010] The heavy metal micro-nano particles are at least two kinds, serving as core layer additives and shell layer additives respectively;
[0011] The heavy metal micro-nano particles are nano-scale and micro-scale particles of non-lead heavy metal oxides;
[0012] The surface modifier includes any one or a mixture of two or more of hexadecyltrimethylammonium bromide, tannic acid, chitosan, polydopamine or a silane coupling agent;
[0013] Due to the huge density difference between heavy metal micro-nano particles and polymer spinning solution, heavy metal micro-nano particles without surface modification will quickly settle even after being uniformly dispersed in the polymer spinning solution, which is not conducive to the electrospinning process; the purpose of this step is to enhance the interaction with the polymer spinning solution and inhibit or slow down the sedimentation of heavy metal micro-nano particles;
[0014] S2 Preparation of polymer electrospinning precursor solution: dissolving the polymer by its good solvent to form a homogeneous polymer spinning solution, and then adding the surface-modified heavy metal micro-nanoparticles obtained in step S1 as core layer additives and shell layer additives to the polymer spinning solution respectively and mixing them evenly to obtain a shell layer spinning solution precursor and a core layer spinning solution precursor respectively;
[0015] The polymer in the polymer electrospinning precursor solution includes any one or a mixture of two or more of polyurethane, polyacrylonitrile, polylactic acid, polyvinyl alcohol, polymethyl methacrylate, polycaprolactone, starch or fish gelatin;
[0016] S3 coaxial electrospinning: The shell layer spinning liquid precursor and the core layer spinning liquid precursor are respectively injected into the two syringes of the electrospinning device. Under the action of a high voltage electric field of 15 to 30 kV, the shell layer spinning liquid precursor and the core layer spinning liquid precursor solutions are sprayed to form nanofibers, which are then collected to form a film.
[0017] Preferably, after step S3, step S4 post-treatment is performed, which specifically includes the following steps: heat treatment or cross-linking treatment of the collected nanofiber membrane to improve its mechanical properties and durability.
[0018] Preferably, the heavy metal micro-nano particles in step S1 include single substances, salts and metal oxides of tungsten, bismuth, tantalum, barium, ytterbium, gadolinium, samarium and cerium; and the particle size distribution of the heavy metal micro-nano particles is 100nm-2μm.
[0019] Preferably, in step S1, the surface modifier modification operation is to fully mix the excess surface modifier with the heavy metal micro-nanoparticles and then separate the excess surface modifier.
[0020] Preferably, the good solvent in step S2 includes any one of DMF, acetone, chloroform, n-hexane, tetrahydrofuran, or a mixture of two or more thereof.
[0021] Preferably, in step S2, the concentration of the polymer spinning solution is 30-50wt%; the ratio of the added mass of the core layer additive and the shell layer additive to the mass of the polymer spinning solution is 0.3:1-0.5:1.
[0022] Preferably, in step S3, the ratio of the propulsion flow rate of the shell layer spinning solution precursor to the propulsion flow rate of the core layer spinning solution precursor is 3:1.
[0023] Preferably, in step S3, the shell layer spinning liquid precursor and the core layer spinning liquid precursor solution are respectively connected to the outer nozzle and the inner nozzle of the electrospinning device, the coaxial needle is pulled and fixed on the reciprocating platform and connected to a DC high-voltage power supply, and the tin foil is wrapped on a metal roller receiving device as a collection device for the coaxial nanofiber membrane.
[0024] Preferably, in step S3, the distance between the membrane receiver and the spinneret of the electrospinning device is 10-30 cm, the spinning temperature is 20-35° C., and the spinning humidity is 40-70%.
[0025] In a second aspect, the present invention provides a core-shell structured γ-ray shielding nanofiber membrane, which is prepared by the preparation method described in the first aspect.
[0026] A single fiber of the nanofiber membrane is a core-shell structure, including a shell layer and a core layer; both the shell layer and the core layer of the single fiber of the nanofiber membrane contain non-lead heavy metal shielding elements.
[0027] The beneficial effects achieved by the present invention are:
[0028] The nanofiber membrane involved in the present invention consists of two parts: an inner core and an outer shell. The outer shell is composed of heavy metal micro-nano particles and high molecular polymers with medium and high energy gamma ray shielding capabilities, and mainly plays the role of shielding and attenuating the energy of medium and high energy gamma rays; the inner core is mainly composed of heavy metal micro-nano particles and light high molecular polymers with medium and low energy gamma ray shielding capabilities, and mainly effectively absorbs the energy of gamma rays and medium and low energy gamma rays attenuated by the outer shell layer. The high molecular polymers in the shell layer and the core layer play a skeleton role, giving the electrospinning membrane overall flexibility and mechanical properties. After the gamma rays of a certain medium and high energy segment are absorbed by the heavy metal particles in the shell layer, a part of them is effectively absorbed by the heavy metal particles through the photoelectric effect, and the other part, which is mainly the rays in the medium and low energy segment, passes through the shell layer to reach the core layer, and is attenuated and absorbed by the heavy metal micro-nano particles in the core layer with medium and low energy segment gamma ray shielding capabilities, thereby achieving effective absorption, attenuation and absorption of medium and high energy segment gamma rays. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention is further described below in conjunction with some drawings, including but not limited to the heavy metal micro-nano particles and electrospinning membranes shown in the following figures.
[0030] Figure 1 This is a scanning electron microscope image of bismuth oxide powder.
[0031] Figure 2 This is a scanning electron microscope image of tungsten oxide powder.
[0032] Figure 3 This is a scanning electron microscope image of tantalum oxide powder.
[0033] Figure 4 Scanning electron micrograph of tantalum oxide / PAN-bismuth oxide / PU nanofiber membrane with core-shell structure.
[0034] Figure 5 This is a scanning electron micrograph of a single core-shell structured tantalum oxide / PAN-bismuth oxide / PU nanofiber. DETAILED DESCRIPTION
[0035] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific embodiments.
[0036] Example 1
[0037] This embodiment aims to prepare a gamma-ray shielding nanofiber membrane with a core-shell structure, wherein the shell layer is based on polyacrylonitrile (PAN) and bismuth oxide (Bi2O3) is a filling shielding component; the core layer is based on polyurethane (PU) and tantalum oxide (Ta2O5) is a shielding component.
[0038] The specific preparation process is as follows:
[0039] S1: Modify the surface of Ta2O5 and Bi2O3 by coupling agent modification method. Specifically: Disperse 10ml KH570 in 190ml 50% ethanol aqueous solution to obtain KH570 dispersion. Take 100ml of the above dispersion, add 30g Bi2O3 powder, continue stirring for 10h, then evaporate the ethanol aqueous solution, and finally obtain Bi2O3 with KH570 surface modification; Same as Bi2O3 modification step, take 100ml KH570 aqueous dispersion, add 30g Ta2O5 powder, continue stirring for 10h, then evaporate the ethanol aqueous solution, and finally obtain Ta2O5 with KH570 surface modification.
[0040] S2: Preparation of nuclear layer solution.
[0041] 40 g of polyurethane (PU) powder was weighed and dissolved in 60 g of N,N-dimethylformamide (DMF) at a concentration of 40 wt %.
[0042] 40 g of the modified Ta2O5 nanoparticles were added to the above PU solution, and the nanoparticles were evenly dispersed in the PU solution by ultrasonic treatment, cell disruption, homogenization with a homogenizer, and vigorous stirring.
[0043] The prepared core layer solution is injected into the inner nozzle through the electrospinning equipment to prepare for the next electrospinning process.
[0044] S3: Preparation of shell solution:
[0045] 40 g of polyacrylonitrile (PAN) powder was weighed and dissolved in 60 g of organic solvent DMF to obtain a PU solution with a concentration of 40 wt %.
[0046] 40 g of the modified Bi2O3 nanoparticles were added to the above PAN solution, and the nanoparticles were evenly dispersed in the PAN solution by ultrasonic treatment, cell disruption, homogenization with a homogenizer, and vigorous stirring.
[0047] The prepared shell layer solution is injected into the outer nozzle through the electrospinning equipment and electrospun simultaneously with the core layer solution.
[0048] S4: Electrospinning:
[0049] Under the action of high voltage electric field, core layer and shell layer solutions are ejected from inner and outer nozzles simultaneously to form nanofibers with core-shell structure, which are deposited on the collector and form a membrane structure. The propulsion flow rate of shell layer spinning solution is 3mL / min, and the propulsion speed of core layer spinning solution is set to 1mL / min. The working voltage is 25kV, the distance between membrane receiver and spinneret is 20cm, the spinning temperature is 27℃, and the spinning humidity is 55%.
[0050] S5: Collection and post-processing:
[0051] The nanofiber membrane on the collector needs to be collected and post-processed to improve its performance.
[0052] First, the nanofiber membrane is removed from the collector and dried as needed.
[0053] Then, the nanofiber membrane was placed in a 55°C oven for heat treatment to improve its mechanical properties and durability.
[0054] Finally, the nanofiber membrane was treated with cross-linking agent glutaraldehyde vapor to improve its chemical stability and solvent resistance.
[0055] Through the above steps, this embodiment successfully prepared a γ-ray shielding nanofiber membrane with a core-shell structure, wherein the shell layer is based on PAN and Bi2O3 is a filling shielding component; the core layer is based on PU and Ta2O5 is a shielding component. The nanofiber membrane has light weight, high-efficiency shielding performance (81keV γ-rays) and good mechanical properties. The specific properties are shown in Table 1 below, and it is suitable for nuclear radiation scene applications under air and moisture permeability conditions.
[0056] Table 1. Gamma ray shielding performance of Bi2O3-Ta2O5 core-shell structure nanofiber membrane
[0057]
[0058] Example 2
[0059] This embodiment aims to prepare a gamma-ray shielding nanofiber membrane with a core-shell structure, wherein the shell layer is based on polyurethane (PU) and tungsten oxide (WO3) is the filling shielding component; the core layer is based on polylactic acid (PLA) and samarium oxide (Sm2O3) is the shielding component.
[0060] The specific preparation process is as follows:
[0061] S1: Modify the surface of WO3 and Sm2O3 by using a surface modifier, specifically 10wt% tannic acid can be used to complete the modification. Pretreatment of tannic acid:
[0062] Dissolve 10g of tannic acid in 90g of ethanol aqueous solution (50wt%) to form a tannic acid solution. Heating, stirring or ultrasonic treatment can be used to help tannic acid dissolve better. Add 30g of tungsten oxide nanoparticles to the above tannic acid solution and stir or ultrasonicate for at least 5h to adsorb tannic acid molecules on the surface of WO3 particles. The modification process can be carried out at room temperature or under heating conditions to improve the modification efficiency. After the modification is completed, the complex is separated from the solution by centrifugation or filtration, as follows: wash multiple times with 50ml of solvent (such as water or ethanol) each time to remove unadsorbed tannic acid and surface adsorbed impurities, and finally vacuum dry at 60℃ for 10h. The surface modification treatment of Sm2O3 nanoparticles is the same as above.
[0063] S2: Preparation of core layer and shell layer polymer spinning solution:
[0064] Preparation of core layer polymer spinning solution: core layer matrix material is polylactic acid (PLA) powder; core layer polymer spinning solution: a mixture of PLA powder (30g) and DMF solvent (70g), that is, the mass percentage of PLA is 30%; core layer additive is WO3 nanoparticles: 30g WO3 is dispersed in 30g PLA solution, and WO3 is evenly dispersed in the PLA polymer solution through ultrasonic, homogenization and stirring (treatment time is 4h).
[0065] Preparation of shell polymer spinning solution: Shell matrix material is polyurethane (PU) powder; Shell solution: mixture of PU powder and DMF solvent. The specific operation steps are as follows:
[0066] Weigh 30 g of PU powder and dissolve it in 70 g of DMF solvent to obtain a PU solution with a concentration of 30 wt%;
[0067] 30 g of the dried tannic acid-WO3 complex was added to 30 g of the above PU solution, and the complex was evenly dispersed in the PU solution by stirring and ultrasonic treatment for 3 hours to obtain a PU-WO3 polymer spinning solution with a concentration of 50 wt%.
[0068] S3: Preparation of core-shell structured nanofibers by coaxial electrospinning:
[0069] Under the action of the high voltage electric field, the core layer and shell layer solutions are ejected from the inner and outer nozzles at the same time to form nanofibers with a core-shell structure. The nanofibers are deposited on the collector and form a membrane structure. The propulsion flow rate of the shell layer spinning solution is 3mL / min, and the propulsion speed of the core layer spinning solution is set to 1mL / min. The nanofiber membrane on the collector is collected and post-processed to improve its performance. The working voltage of the electrospinning machine is 30kV, the distance between the membrane receiver and the spinneret is 25cm, the spinning temperature is 30℃, and the spinning humidity is 50%.
[0070] First, the nanofiber membrane is removed from the collector and dried.
[0071] Then, the nanofiber membrane was placed in an oven at 60°C for heat treatment to improve its mechanical properties and durability.
[0072] Finally, it was treated with the cross-linking agent glutaraldehyde vapor to improve its chemical stability and solvent resistance.
[0073] Through the above steps, this embodiment successfully prepared a γ-ray shielding nanofiber membrane with a core-shell structure, wherein the shell layer is based on PLA and Sm2O3 is a filling shielding component; the core layer is based on PU and WO3 is a shielding component. The nanofiber membrane has light weight, high-efficiency shielding performance (81keV γ-rays) and good mechanical properties. The specific properties are shown in Table 2 below, and it is suitable for nuclear radiation scene applications under air and moisture permeability conditions.
[0074] Table 2. Gamma-ray shielding performance of WO3-Sm2O3 core-shell structure nanofiber membrane
[0075]
[0076] Example 3
[0077] S1: The surface of gadolinium oxide (Gd2O3) and cerium dioxide (CeO2) micro-nano particles was modified by coupling agent modification method.
[0078] KH550 is selected to be mixed with CeO2 micro-nano particles and Gd2O3 micro-nano particles, and stirred at room temperature to fully allow the coupling agent molecules to be adsorbed on the surfaces of CeO2 and Gd2O3 particles; the unadsorbed coupling agent is removed through centrifugation and washing steps to obtain modified CeO2 and Gd2O3.
[0079] The specific steps are as follows: 10g KH550 is dissolved in 90g ethanol aqueous solution (50wt%) to form KH550 ethanol aqueous solution. 30g Gd2O3 nanoparticles are added to the above KH550 solution, and the KH550 molecules are adsorbed on the surface of the Gd2O3 particles by stirring or ultrasonic treatment for at least 5h. The modification process is carried out by rapid stirring to improve the modification efficiency, and the stirring speed is 500r / min. After the modification is completed, the complex is separated from the solution by centrifugation and filtration, and washed several times to remove the unadsorbed KH550 and impurities adsorbed on the surface, and finally vacuum dried at 60°C for 10h. The surface modification treatment method of CeO2 nanoparticles is the same as above.
[0080] S2: Preparation of core layer solution. Core layer material: polycaprolactone (PCL) powder; core layer solution: PCL powder (20 g) dissolved in DMF solvent (80 g), i.e., the mass percentage of PCL is 20%. Core layer additive: KH550 modified Gd2O3 nanoparticles, 30 g of gadolinium oxide is dispersed in 30 g of PCL solution, and Gd2O3 is evenly dispersed in the PCL polymer solution by ultrasonic, homogenization and stirring for 4 hours.
[0081] S3: Preparation of shell solution. Shell material: polymethyl methacrylate (PMMA) powder; shell solution: a mixture of PMMA powder and DMF solvent. The specific operation steps are as follows:
[0082] Weigh 30 g of PMMA powder and dissolve it in 70 g of DMF solvent to obtain a PMMA solution with a concentration of 30 wt%;
[0083] 30 g of the dried KH550-CeO2 composite was added to 30 g of the above PMMA solution, and the composite was evenly dispersed in the PMMA solution by stirring or ultrasonic treatment for at least 3 hours to obtain a PMMA-CeO2 polymer spinning solution with a concentration of 50 wt%.
[0084] S4: Coaxial electrospinning:
[0085] Under the action of the high voltage electric field, the core layer and shell layer solutions are ejected from the inner and outer nozzles at the same time to form nanofibers with a core-shell structure. The nanofibers are deposited on the collector and form a membrane structure. The propulsion flow rate of the shell layer spinning solution is 3mL / min, and the propulsion speed of the core layer spinning solution is set to 1mL / min. The working voltage of the electrospinning machine is 28kV, the distance between the membrane receiver and the spinneret is 26cm, the spinning temperature is 32℃, and the spinning humidity is 60%.
[0086] First, the nanofiber membrane is removed from the collector and dried.
[0087] Then, the nanofiber membrane was placed in an oven at 60°C for heat treatment to improve its mechanical properties and durability.
[0088] Finally, it was treated with the cross-linking agent glutaraldehyde vapor to improve its chemical stability and solvent resistance.
[0089] Through the above steps, this embodiment successfully prepared a γ-ray shielding nanofiber membrane with a core-shell structure, wherein the shell layer is based on PMMA and CeO2 is a filling shielding component; the core layer is based on PCL and Gd2O3 is a shielding component. The nanofiber membrane has light weight, high-efficiency shielding performance (81keV γ-rays) and good mechanical properties. The specific properties are shown in Table 3 below, and it is suitable for nuclear radiation scene applications under air and moisture permeability conditions.
[0090] Table 3. Gamma ray shielding performance of Gd2O3-CeO2 core-shell structure nanofiber membrane
[0091]
[0092] In summary, the core-shell structured nanofiber membrane obtained according to the production and preparation method of the present invention has the following characteristics: light weight and high efficiency (the core-shell structure design enables the nanofiber membrane to provide efficient γ-ray shielding effect while maintaining light weight), excellent mechanical properties (the shell layer of the nanofiber membrane is usually composed of polymers, which gives the material good flexibility and mechanical strength), good processing performance (electrospinning technology allows flexible adjustment of the diameter, morphology and arrangement of the nanofibers, so that the performance of the material can be customized according to specific application requirements), environmental friendliness (compared with traditional γ-ray shielding materials, the core-shell structured nanofiber membrane may require less energy and raw materials during the preparation process, and may reduce the emission of environmentally harmful substances, meeting the requirements of sustainable development) and multifunctionality (this nanofiber membrane can not only be used as a γ-ray shielding material, but also can be modified or compounded with other functional materials to give it additional properties, such as antibacterial, self-cleaning or sensor functions, thereby broadening its application range).
[0093] Its application prospects are also very broad, including but not limited to personal protective equipment (can be used to manufacture protective clothing, helmets, goggles, etc. to provide effective gamma ray protection for personnel engaged in radioactive work), medical equipment (for the shells of radioactive treatment and diagnostic equipment, such as radiotherapy machines, CT scanning rooms, and containers for transporting radioactive materials), aerospace fields (for the shells or components of satellites, spacecraft and space stations to protect electronic equipment and astronauts from the effects of cosmic rays), nuclear facilities, etc.
[0094] In summary, the nanofiber membrane prepared by "a core-shell structured γ-ray shielding nanofiber membrane and its preparation method" has broad application prospects in the field of radiation protection, and through further research and development, it is expected to play an important role in more fields.
[0095] The above embodiments will help those skilled in the art to further understand the content of the present invention, but do not limit the present invention in any form. It should be pointed out that, for all those skilled in the art, without departing from the concept of the present invention, the present invention may also make several formal deformations and improvements (such as content, thickness, drying procedure, etc.), which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a core-shell structured γ-ray shielding nanofiber membrane, characterized in that: The following steps are involved: S1 Surface modification of heavy metal micro-nano particles: Use a surface modifier to modify the surface of heavy metal micro-nano particles so that the surface of the heavy metal micro-nano particles has functional groups; The heavy metal micro-nano particles are at least two kinds, serving as core layer additives and shell layer additives respectively; The heavy metal micro-nano particles are nano-scale and micro-scale particles of non-lead heavy metal oxides; The surface modifier includes any one or a mixture of two or more of hexadecyltrimethylammonium bromide, tannic acid, chitosan, polydopamine or a silane coupling agent; S2 Preparation of polymer electrospinning precursor solution: dissolving the polymer by its good solvent to form a homogeneous polymer spinning solution, and then adding the surface-modified heavy metal micro-nanoparticles obtained in step S1 as core layer additives and shell layer additives to the polymer spinning solution respectively and mixing them evenly to obtain a shell layer spinning solution precursor and a core layer spinning solution precursor respectively; The polymer in the polymer electrospinning precursor solution includes any one or more of polyurethane, polyacrylonitrile, polylactic acid, polyvinyl alcohol, polymethyl methacrylate, polycaprolactone, starch or fish gelatin; S3 coaxial electrospinning: The shell layer spinning liquid precursor and the core layer spinning liquid precursor are respectively injected into the two syringes of the electrospinning device. Under the action of a high voltage electric field of 15 to 30 kV, the shell layer spinning liquid precursor and the core layer spinning liquid precursor solutions are sprayed to form nanofibers, which are then collected to form a film.
2. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: After step S3, step S4 post-processing is performed, which specifically includes the following steps: heat treatment or cross-linking treatment is performed on the collected nanofiber membrane to improve its mechanical properties and durability.
3. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: The heavy metal micro-nano particles in step S1 include single substances, salts and metal oxides of tungsten, bismuth, tantalum, barium, ytterbium, gadolinium, samarium and cerium; the particle size distribution of the heavy metal micro-nano particles is 100nm-2μm.
4. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: In the step S1, the surface modifier modification operation is to fully mix the excess surface modifier with the heavy metal micro-nano particles, and then separate the excess surface modifier.
5. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: The good solvent in step S2 includes any one of DMF, acetone, chloroform, n-hexane, and tetrahydrofuran, or a mixture of two or more thereof.
6. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: In the step S2, the concentration of the polymer spinning solution is 30-50wt%; the ratio of the added mass of the core layer additive and the shell layer additive to the mass of the polymer spinning solution is 0.3:1-0.5:
1.
7. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: In the step S3, the ratio of the propulsion flow rate of the shell layer spinning solution precursor to the propulsion flow rate of the core layer spinning solution precursor is 3:
1.
8. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: In step S3, the shell layer spinning liquid precursor and the core layer spinning liquid precursor solution are respectively connected to the outer nozzle and the inner nozzle of the electrospinning device, the coaxial needle is pulled and fixed on the reciprocating platform and connected to a DC high-voltage power supply, and the tin foil is wrapped on a metal roller receiving device as a collection device for the coaxial nanofiber membrane.
9. The method for preparing the core-shell structured γ-ray shielding nanofiber membrane according to claim 1, characterized in that: In the step S3, the distance between the membrane receiver and the spinneret of the electrospinning device is 10-30 cm, the spinning temperature is 20-35° C., and the spinning humidity is 40-70%.
10. A core-shell structured γ-ray shielding nanofiber membrane, prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electromagnetic shielding nano-fiber and preparation method thereof
CN111455492A
Anti-nuclear radiation sheath-core composite fiber and preparation method thereof
CN112144147A
Preparation method of core-shell structure tungsten / gadolinium oxide functional fiber for X and gamma ray protection
CN112831855A
Core-shell structure shielding material and preparation method thereof
CN115305598A
Nuclear protection nanofiber aerogel with bionic structure and preparation method thereof
CN115478430A
Cited By
Bifunctional gypsum admixture based on plant polyphenol-nanoparticles and preparation method thereof
CN119684029A
Shape memory polymer fiber membrane and preparation method thereof, shape memory polymer scaffold and preparation method and application thereof
CN121197519A
A lead-free X, gamma ray flexible shielding material and a preparation method thereof
CN122822427A